Tamara Drewe [videorecording (DVD)] - Frears, Stephen; Arterton, Gemma; Evans, Luke, 1979-; Allam, Roger; Cooper, Dominic, 1978-; Greig, Tamsin, 1967-; Simmonds, Posy (Sony Pictures Home Entertainment, 2011)
Tamara Drewe was an ugly duckling when she left town. Years later, she is a sexy swan who has returned to her hometown after the death of her mother. Her plans are to refurbish the family home and put it on the market. It isn't long before Tamara finds herself pursued by three men from her past: Andy, her former boyfriend, Ben, the drummer with a local rock band, and Nicholas, the boy she was infatuated with in her teens.